Preservice Turkish language teachers’ attitudes toward Anatolian dialects - İzzet Şeref (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study aimed to reveal preservice Turkish Language teachers' attitudes toward the use of Anatolian dialects in education in terms of their genders and years at university. The participants of the study are 201 preservice teachers who are 1st, 2nd, 3rd and 4th-year students studying at Turkish Language Teaching undergraduate program at Tokat Gaziosmanpasa University in the 2017-2018 academic year. The study is a correlational survey employing a descriptive research method. The data of the study were collected employing a scale named Attitude Scale Toward Anatolian Dialects. Using SPSS 22.0, t-Test for independent samples and One-Way ANOVA for independent samples were employed to analyze the data.  As a result of the study, it is found out that there is a significant difference between the attitudes toward Anatolian dialects in favor of males; and being only between 2nd and 4th-year students, there is a significant difference between the attitudes in favor of 2nd-year students.